2021
DOI: 10.1080/13696998.2021.1877148
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations and healthcare costs associated with rifaximin versus lactulose treatment among commercially insured patients with hepatic encephalopathy in the United States

Abstract: View related articles View Crossmark dataHospitalizations and healthcare costs associated with rifaximin versus lactulose treatment among commercially insured patients with hepatic encephalopathy in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 23 publications
0
27
1
Order By: Relevance
“…An analysis of 2 US claims databases (N = 11,205) indicated that rifaximin (with or without lactulose) decreased absolute annual rates of hepatic encephalopathy-related admissions 33% to 34% compared with lactulose alone, irrespective of adherence to rifaximin (reduction of 49% to 51% vs lactulose alone). 31 Further, hepatic encephalopathy-related hospital days decreased 43% and 57% with rifaximin versus lactulose alone. 31 An analysis of data from a large US Medicare cohort of patients with cirrhosis and a diagnosis of hepatic encephalopathy (2008-2014; N = 49,164) supported the efficacy of hepatic encephalopathy prophylaxis to improve survival and hospitalization-related outcomes (Figure 2).…”
Section: Impact Of Pharmacologic Treatment On Outcomes In Patients Wi...mentioning
confidence: 95%
See 2 more Smart Citations
“…An analysis of 2 US claims databases (N = 11,205) indicated that rifaximin (with or without lactulose) decreased absolute annual rates of hepatic encephalopathy-related admissions 33% to 34% compared with lactulose alone, irrespective of adherence to rifaximin (reduction of 49% to 51% vs lactulose alone). 31 Further, hepatic encephalopathy-related hospital days decreased 43% and 57% with rifaximin versus lactulose alone. 31 An analysis of data from a large US Medicare cohort of patients with cirrhosis and a diagnosis of hepatic encephalopathy (2008-2014; N = 49,164) supported the efficacy of hepatic encephalopathy prophylaxis to improve survival and hospitalization-related outcomes (Figure 2).…”
Section: Impact Of Pharmacologic Treatment On Outcomes In Patients Wi...mentioning
confidence: 95%
“…31 Further, hepatic encephalopathy-related hospital days decreased 43% and 57% with rifaximin versus lactulose alone. 31 An analysis of data from a large US Medicare cohort of patients with cirrhosis and a diagnosis of hepatic encephalopathy (2008-2014; N = 49,164) supported the efficacy of hepatic encephalopathy prophylaxis to improve survival and hospitalization-related outcomes (Figure 2). 22 More than half of patients (57.8%) received lactulose ≥ 90 days; 31.2% received rifaximin or lactulose < 90 days; and 19.6% received rifaximin monotherapy ≥ 90 days.…”
Section: Impact Of Pharmacologic Treatment On Outcomes In Patients Wi...mentioning
confidence: 95%
See 1 more Smart Citation
“…A recent analysis by Volk et al using 2 large private insurance databases found an average cost of a hospital stay for HE of USD $29,063 to $34,810 during the study period (2014-2019). 69 Readmissions multiply the burden of hospitalization. HE is the strongest risk factor for readmission.…”
Section: Transjugular Intrahepatic Portosystemic Shuntsmentioning
confidence: 99%
“…[ 19 , 20 ] Recent studies have pointed out that the total cost of hospitalization in patients with HE treated with rifaximin is not higher than that in the lactulose treatment group, indicating the high application potential of rifaximin in HE. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%